Addressing transportation and environmental externalities with economics: Are policy makers listening?. (October 2020) - Lindsey, Robin; Santos, Georgina
Abstract: A literature review reveals that economists have had limited success in promoting economically efficient transportation and environmental externality policies. Evidence shows that policy makers are more open to using taxes and cap-and-trade systems to combat climate change than levying tolls to manage traffic congestion. Although carbon taxes are too low, and caps on tradable permits too high, to induce significant Greenhouse Gas (GHG) emissions reductions, governments at all levels are starting to implement these instruments, and climate change is now on the international political agenda as the Paris Agreement demonstrates. By contrast, congestion charging is rare. One reason may be that the science of climate change has become virtually impossible to ignore. Another is that GHG concentrations are cumulative, and the consequences of climate change are global, irreversible and potentially catastrophic. Traffic congestion is localized and transient, and more of an inconvenience than a threat to life. Responsibility for transportation policy is also often divided across multiple levels of government. These differences may explain why the use of economic instruments has been more widespread in dealing with climate change than with congestion. Highlights: Economists' advice has been more influential in formulating climate-change policy than managing traffic congestion. Climate change is perceived to be a more urgent problem than traffic congestion. Climate change is a global problem, whereas congestion is a local problem. Climate change policy includes taxes and tradable permits. Congestion pricing remains limited to a few programs.